Clonidine prevents development of hypertension in N (Omega)-Nitro-L-Arginine-treated rats - Oktar, Sueleyman; Ilhan, Selcuk; Aksulu, Hakki Engin (Kare Publ, 2008)
Objective: Although there are some evidences on the contribution of increased sympathoadrenergic activity on long-term nitric oxide synthase (NOS) inhibition induced hypertension, the contribution of sympathetic activity to the development of this model of hypertension are not sufficiently studied. The aim of the present study is to investigate the effects of clonidine on blood pressure and vascular alpha-adrenergic receptors in the long-term N (omega)-nitro-L-arginine (L-NNA) treated rats. Methods: Sixty two Wistar rats were randomly divided into 8 groups. All groups were administrated L-NNA and/or clonidine in two different concentrations for ten days. L-NNA was administrated in concentrations of 15 and 45 mg/100ml to L-NNA15 and L-NNA45 groups, respectively. Clonidine was also administrated in concentrations of 150 and 225 mu g/100ml to KLO150 and KLO225 groups, respectively. Blood pressure and heart rates were measured with tail-cuff method and plasma NOx levels with spectrophotometer. The alpha-adrenoreceptors responses were evaluated in thoracic aorta rings in in vitro conditions. Results: Clonidine prevented the L-NNA induced hypertension dose-dependently, but did not effect the heart rates decreased by L-NNA. The heart rates and blood pressure of normotensive rats were not changed by clonidine alone. Plasma NOx levels increased in L-NNA15 group (0.62 +/- 0.11 mu mol/L, p=0.003) but did not change in other groups. The sensitivity of aorta to phenylephrine (-7.33 +/- 0.11 mu mol/L, p=0.001) and clonidine (-7.60 +/- 0.27 mu mol/L, p=0.003) in L-NNA45 group and phenylephrine (-6.94 +/- 0.13 mu mol/L, p=0.002) in L-NNA15 group increased. The sensitivity of aorta to phenylephrine (7.93 +/- 0.16 mu mol/L, p=0.001) in KLO225 group and to clonidine (-7.20 +/- 0.10 mu mol/L, p=0.009) in KLO150 group increased. Conclusion: This study supports the idea suggesting that symphathetic nervous system activation is partly responsible for the development of the long-term NOS inhibition induced hypertension. In conclusion, it was shown for the first time that clonidine prevents the development of long-term NOS inhibition induced hypertension dose-dependently.
Klonidin N (Omega)-Nitro-L-Arjinin aracili hipertansiyon gelişimini önler
Keywords: hypertension; nitric oxide; clonidine; sympathetic activity; alpha adrenergic receptors